Investigating the Mediating Effect of Credit Rating on the Relationship between Corporate Governance Quality and Stock Liquidity based on the Composite Liquidity Approach - Amin Pourrezaei Nav; Hamzeh Didar; Farzad Ghayour (Pizhūhish/hā-yi ḥisābdārī-i mālī)
Considering that one of the factors influencing credit ratings is the quality of corporate governance and that credit ratings affect stock liquidity in the capital market by influencing investors' decisions, this study aims to investigate the mediating effect of credit ratings on the relationship between corporate governance quality and stock liquidity over 10 years from 2013 to 2022. In this regard, for the first time in Iran, a composite liquidity index was used to calculate stock liquidity. The data collection method involved document analysis and reference to databases, and the data analysis method was inferential. To test the research hypotheses, a panel data model was used. Emphasizing the reverse structure of the composite liquidity measure, the findings of the study indicated that corporate governance quality has a positive and significant impact on stock liquidity and that credit ratings play a partial mediating role in the relationship between corporate governance quality and stock liquidity.IntroductionThe purpose of this study was to investigate the mediating effect of credit rating on the relationship between the quality of corporate governance and stock liquidity. In this regard, it was first noted that the existence of a highly liquid market is important and necessary to encourage and attract investors to transfer wealth to such markets. This is because one of the key drivers of any country's economy is its capital market, and a crucial factor in these markets is stock liquidity. Therefore, understanding the factors that contribute to the creation of a highly liquid market is of great importance. Research literature indicates that information asymmetry is a phenomenon that reduces the level of awareness among market participants. In such cases, investors cannot accurately assess the value of a company's shares and make rational decisions to buy or sell them. Additionally, it has been noted that accounting information alone cannot adequately evaluate a company's performance or serve as a reliable basis for investors' decisions. In this context, corporate governance is presented as a set of relationships between the company's management, the board of directors, shareholders, and other stakeholders. It is argued that corporate governance, by improving company performance, significantly enhances the quality of information provided to the market and, by reducing information asymmetry, increases stock liquidity. Moreover, the advantages of rating institutions have been examined both theoretically and empirically. It has been stated that these institutions, by accessing confidential information and transferring it to the market in the form of credit ratings, can influence investors' decision-making. Additionally, corporate governance is recognized as an influential factor in the credit rating process.Methods & MaterialThis research is applied in nature and employs multivariate regression analysis to examine the relationship between the study variables. The research methodology is of an ex post facto type. Additionally, since it aims to evaluate the relationship between two or more variables, it is descriptive-correlational in nature. Based on the criteria applied for selecting the statistical sample, 101 companies were chosen for the period from 2013 to 2022 to test the hypotheses. Data analysis was conducted using Stata and EViews software.FindingThe results indicate the presence of an inverse and significant relationship between the quality of corporate governance and credit rating with the composite liquidity criterion. Considering the inverse structure of the composite liquidity index and the negative and significant relationship between the quality of corporate governance and credit rating with this index, i.e., composite liquidity, it can be concluded that higher corporate governance quality scores and, consequently, higher credit ratings are associated with higher share liquidity. Conversely, lower governance quality scores and credit ratings correspond to lower share liquidity. The obtained results indicate that credit rating as a mediating variable is a partial mediating factor in the relationship between the quality of corporate governance and stock liquidity. In this way, the third hypothesis of the research is confirmed, and the quality of corporate governance has both a direct and an indirect effect on the liquidity of stocks. It can be said that the quality of corporate governance in companies with a high credit rating increases the liquidity of the companies' shares.Disscussion and Conclusion The results indicate that credit rating, as a mediating variable, is a partial mediator in the relationship between the quality of corporate governance and stock liquidity. Based on the findings, it can be stated that corporate governance directly influences the liquidity of a company's shares. Additionally, by achieving a higher credit rating, corporate governance indirectly encourages investors to buy and sell the company's shares, thereby increasing their liquidity.